A Life-Course Perspective on Incarcerated Women's Views on Adulthood. Issue 5 (20th October 2018) - Umamaheswar, Janani
Abstract : Drawing on 35 in-depth interviews with incarcerated women, supplemented by mail correspondence with a sub-sample of these women, I explore how the participants interpret their early life-course experiences when reflecting on their transition to adulthood and, subsequently, their views on adult roles and responsibilities. The women's narratives indicate that early experiences with trauma, along with premature entries into adult roles, result in a disorganized transition to adulthood. The findings also suggest that the women's accelerated transitions to adulthood shape their views on adult roles, pointing to a need to incorporate discussions of age-normative timetables in efforts to assist at-risk and incarcerated women.